Adaptive constraint-guided surrogate enhanced evolutionary algorithm for horizontal well placement optimization in oil reservoir - Dai, Qinyang; Zhang, Liming; Wang, Peng; Zhang, Kai; Chen, Guodong; Chen, Zhangxing; Xue, Xiaoming; Wang, Jian; Liu, Chen; Yan, Xia; Liu, Piyang; Wu, Dawei; et al. (Computers & geosciences, 2025)
In the face of escalating global energy demands, this study introduces an Adaptive Constraint-Guided Surrogate Enhanced Evolutionary Algorithm (ACG-EBS) for optimizing horizontal well placements in oil reservoirs. Addressing the complex challenge of maximizing oil production, the ACG-EBS integrates geological, engineering, and economic considerations into a novel optimization framework. This algorithm stands out for its adept navigation through a complex and discrete decision space of horizontal well placements, an area where traditional methods often encounter challenges. Key innovations include the Adaptive Constraint Initialization Mechanism (ACIM) and the Evolutionary Constraint-Tailored Candidate Refinement strategy (ECTCR), which collectively elevate the feasibility of candidate solutions. An enhanced balance strategy harmonizes comprehensive and niche surrogate models, optimizing the balance between exploration and exploitation. Through testing on both two-dimensional and three-dimensional reservoir models, the ACG-EBS has proven highly effective in identifying optimal well placements that align with field deployment realities and maximize economic returns. This contribution significantly supports the ongoing evolution of oilfield development optimization, showcasing the algorithm's potential to enhance oil production and economic outcomes. •A novel ACG-EBS is proposed for optimizing horizontal well placement in reservoirs.•ACIM and ECTCR are designed to adaptively enhance feasibility under constraints.•A dual surrogate mechanism is developed to balance exploration and exploitation.•Superior performance is demonstrated in cases, boosting oil production.•Workflow adaptable to other complex optimization challenges in the oil industry.